THE INFLUENCE OF READING INTEREST ON GPA OF STUDENT OF BUILDING ENGINEERING EDUCATION OF PALANGKARAYA UNIVERSITY IN EVEN SEMESTER ACADEMIC YEAR 2012/2013 - Trissan, Whendy (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
“No day without reading